UDK 664.34:637.144 PHYSICAL-CHEMICAL ANALYSIS OF OIL TAKEN FROM SEEDS OF SAFFLOWER - Adashev, Bexzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Considering the growing demand for vegetable oils today, after the autumn wheat harvest, vacant land areas are being used to grow secondary crops such as sunflower, safflower, sesame, soybean, and other unconventional oilseeds. The extracted oilseeds are then processed to meet the population’s needs for vegetable oils and fat products.